2004
DOI: 10.1016/j.pain.2004.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spouse-assisted coping skills training and exercise training in patients with osteoarthritic knee pain: a randomized controlled study

Abstract: This study tested the separate and combined effects of spouse-assisted pain coping skills training (SA-CST) and exercise training (ET) in a sample of patients having persistent osteoarthritic knee pain. Seventy-two married osteoarthritis (OA) patients with persistent knee pain and their spouses were randomly assigned to: SA-CST alone, SA-CST plus ET, ET alone, or standard care (SC). Patients in SA-CST alone, together with their spouses, attended 12 weekly, 2-h group sessions for training in pain coping and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
206
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 264 publications
(215 citation statements)
references
References 48 publications
4
206
0
5
Order By: Relevance
“…RC led to the greatest improvements in interpersonal outcomes for couples, and had some of the strongest effect sizes overall, which suggests that this may be an important area of need for couples living with chronic illness. Another key observation was that many couples interventions achieved greater effects than the same or similar patient-only intervention across emotional [42], interpersonal [37,43,44], cognitive [41,49], and somatic outcomes [46,48]. This suggests that partner-inclusion may provide benefits beyond that of the content of the intervention itself.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…RC led to the greatest improvements in interpersonal outcomes for couples, and had some of the strongest effect sizes overall, which suggests that this may be an important area of need for couples living with chronic illness. Another key observation was that many couples interventions achieved greater effects than the same or similar patient-only intervention across emotional [42], interpersonal [37,43,44], cognitive [41,49], and somatic outcomes [46,48]. This suggests that partner-inclusion may provide benefits beyond that of the content of the intervention itself.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies compared the couples intervention with a patient-only intervention [35,36,37,38,39,40], eight studies used a patient-only comparison group and a usual care control group [41,42,43,44,45,46,47,48], one study compared two types of couples interventions with a patient-alone comparison group [49], and the remaining twenty compared a couples intervention with usual care or waiting-list controls. Twenty-eight studies reported effect sizes, or provided information to calculate effect sizes.…”
Section: Main Descriptivesmentioning
confidence: 99%
See 3 more Smart Citations